DAMPAK OSTEOMIELITIS TERHADAP PENYEMBUHAN LUKA: PERAN DEBRIDEMEN BEDAH DAN DISRUPSI BIOFILM - Zulkarnain, Octo; Farida, Denis; Nur Cahyanto, Heri (Jurnal Penelitian Keperawatan Kontemporer, 2025)
Background: Increasing complaints about poor nursing care have prompted the investigation of possible reasons for this phenomenon. One of the factors that influence caring behavior is the practice environment, such as workload. Aim: To analyze the relationship between workload and nurse caring behavior. Method: This study was a correlational analytic study with a cross sectional approach. The sample in this study amounted to 73 people. The sample was taken by using purposive sampling technique. The results of the study were tested with the Pearson statistical test with a significance of α = <0.05 using the SPSS v.23 program. The research instrument used a workload questionnaire and the CBAS (Caring Behaviors Assessment Scale). This research was conducted at Bhayangkara Makassar Hospital. Results: The results of the Pearson correlation test with a level of error (α) = 0.05, obtained p value = 0.011. This means that there is a significant relationship between workload and caring behavior applied by nurses. Conclusion: The lower the workload, the more likely it is for nurses to show caring behavior in providing nursing care.